Best practices in greening transportation at Wageningen University & Research - Luttik, Joke; Maters, Erna (Universitas Diponegoro, 2022)
Key words for the sustainable mobility policy of Wageningen University & Research (WUR) are: safe, healthy, sustainable, accessible, emission reduction and future-focused. WUR mobility policy has three key elements, in the following order of importance: 1) less travel, 2) transition to sustainable modes of transport, and 3) efficient, clean transport. The objective is to further decrease our annual carbon emissions by at least 2%. WUR’s long-term mobility policy is outlined in the Mobility Plan 2030. Measures are focused on encouraging cycling and use of public transport, and discouraging use of fossil fuels for business travel and commuting. Alternatives to air travel and sustainable transport options are facilitated. Examples of promoting sustainable transport are offering e-bike test drives for employees and the introduction of an app for business trips with electric cars, bicycles and public transport. A stricter policy on business travel by train within Europe was implemented, with a Travel Check for staff to find alternatives for air travel. In addition, due to the corona pandemic, WUR drew up a policy on remote working and aims to maximise sustainability benefits of remote work.Keyword: Sustainable transport, sustainable mobility, low-emission vehicles, remote working